2014
DOI: 10.2337/dc13-1608
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Nighttime 2-Hour Suspension of Basal Insulin in Pump-Treated Type 1 Diabetes Even in the Absence of Low Glucose

Abstract: OBJECTIVEAn integrated sensor-augmented pump system has been introduced that interrupts basal insulin infusion for 2 h if patients fail to respond to low-glucose alarms. It has been suggested that such interruptions of basal insulin due to falsely low glucose levels detected by sensor could lead to diabetic ketoacidosis. We hypothesized that random suspension of basal insulin for 2 h in the overnight period would not lead to clinically important increases in blood β-hydroxybutyrate levels despite widely varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Their findings demonstrated that “routine measurement of blood or urine ketones during use of an automated pump suspension system using continuous glucose monitoring, whether threshold based or predictive, is not necessary” (7). These findings confirm and extend those of Sherr et al (8) that were also reported in a recent issue of Diabetes Care .…”
supporting
confidence: 92%
“…Their findings demonstrated that “routine measurement of blood or urine ketones during use of an automated pump suspension system using continuous glucose monitoring, whether threshold based or predictive, is not necessary” (7). These findings confirm and extend those of Sherr et al (8) that were also reported in a recent issue of Diabetes Care .…”
supporting
confidence: 92%
“…18 Previous studies on cessation of rapid delivery of insulin analogues showed that glycemic changes began to occur 1 hour after cessation and were more consistent after 2 or 3 hours. [19][20][21][22] In the case of a 2-hour overnight insulin cessation, glucose levels at the end of the interruption period rose by 16 ± 34 mg/dL at 2 hours and by 63 ± 57 mg/ dL at 4 hours. 19 Another study with a 30-minute interruption reported that the rate of the rise in glucose was 1 mg/dL for each minute the insulin infusion was interrupted, but that the maximum increase was observed 3 hours afterward.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In the case of a 2-hour overnight insulin cessation, glucose levels at the end of the interruption period rose by 16 ± 34 mg/dL at 2 hours and by 63 ± 57 mg/ dL at 4 hours. 19 Another study with a 30-minute interruption reported that the rate of the rise in glucose was 1 mg/dL for each minute the insulin infusion was interrupted, but that the maximum increase was observed 3 hours afterward. 21 In a study of prolonged insulin interruption, β hydroxybutyrate increased in parallel with blood glucose, reaching 1 mmol/L after 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…To address concerns of what could happen if insulin suspension occurred based off the readings of an inaccurate CGM, random 2‐hour preprogrammed insulin suspensions were conducted overnight in a cohort of participants in their home setting as long as pre‐bed blood glucose was <300 mg/dL (16.7 mmol/L) and blood beta‐hydroxybutyrate (BHB) levels were <0.5 mmol/L . A total of 118 suspend nights were compared to 131 non‐suspend nights and showed the morning after suspensions, blood glucose was ~50 mg/dL (2.7 mmol/L) higher but there was no clinically meaningful difference in BHB levels …”
Section: Sensor‐augmented Pump Therapymentioning
confidence: 99%